Management : Perspectives for New Zealand - Inkson, Kerr (Longman, 1998)
This book is designed to introduce the foundations of organisation and management by de-mystifying what may seem to be a vague or distant topic, defininf terminology in clear language and offering case studies that inspire interest in management as an important process in day-to-day life, both within and outside organisations.